Rancang Bangun Sistem Pendaftaran Webinar dan E-Certificate Otomatis - Rahmawati, Eva; Brawijaya, Herlambang; Hertyana, Hylenarti (Jurnal Teknik Informatika UNIKA Santo Thomas, 2024)
In a world increasingly connected digitally, webinars have become a crucial tool for education, training, and information exchange. Along with the rapid growth in the use of webinars, there are often shortcomings in the registration process and distribution of e-certificates, which are inefficient and unsatisfactory. The main issue is the time and human resources required in this process, increasing the risk of errors. Thus, there arises a need for an effective system to manage registration and e-certificate distribution. The automated webinar registration and e-certificate system offer an efficient solution to meet these needs, with the primary goal of maximizing ease of use and operational effectiveness. This system is designed for the automation of the registration process, participant validation, and the creation and distribution of e-certificates, all aimed at enhancing user experience and reducing administrative workload. The development of this system is carried out using the Extreme Programming (XP) method. XP was chosen for its ability to handle changes in needs quickly and efficiently, and its focus on technical quality and customer satisfaction. With a focus on user needs and rapid adaptation to feedback, this system is expected to improve operational efficiency, reduce manual errors, and enhance user satisfaction.